2020
DOI: 10.1177/0733464820979244
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Behaviors in Persons With Alzheimer’s Disease: Associations With Caregiver Sleep and Affect

Abstract: Poor sleep in persons with Alzheimer’s disease (AD) is a common stressor for family caregivers. Retrospective reports support associations between sleep disturbance in persons with AD and worse caregiver mood; however, prospective associations between sleep in persons with AD and caregiver outcomes have not been studied. The current study determined associations between affect and sleep of persons with AD and their caregivers using daily diary data. Multilevel mediation models indicated that sleep in persons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The main symptom of AD is difficulty in short-term memory. As AD progressively worsens, patients exhibit symptoms such as mood and cognition (Lee et al, 2019), motivation loss, speech and language problems (Petti et al, 2020), spatial disorientation (Puthusseryppady et al, 2020), sleep behaviors (Mather et al, 2021), etc. These symptoms lead to a significant decline in quality of life and an increase in care-taker burden (Scheltens et al, 2016;Fulton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The main symptom of AD is difficulty in short-term memory. As AD progressively worsens, patients exhibit symptoms such as mood and cognition (Lee et al, 2019), motivation loss, speech and language problems (Petti et al, 2020), spatial disorientation (Puthusseryppady et al, 2020), sleep behaviors (Mather et al, 2021), etc. These symptoms lead to a significant decline in quality of life and an increase in care-taker burden (Scheltens et al, 2016;Fulton et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…BPSD represents a heterogeneous group of sleep, affective, psychotic, and behavioral symptoms (sundowning, excessive daytime sleepiness, nocturnal wandering) [ 3 ] that occur in the majority of patients with dementia, causing great suffering and increasing the burden on caregivers [ 4 ]. In fact, poor sleep in persons with AD is the most common stressor for family caregivers [ 5 ]. To treat agitation, aggressiveness, delusions, and hallucinations in patients with AD, non-pharmacological approaches are usually preferred, and the use of antipsychotic drugs should be limited due to the increased risk of mortality, stroke, and hallucination, as well as a higher risk of relapse after discontinuation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our population, caregivers took longer to fall asleep than non-caregivers and we know from prior work (Groeger et al, 2014; Mather et al, 2020; McCoy & Strecker, 2011; Narang et al, 2012; Petrov et al, 2018; Spira et al, 2010; Tapp et al, 2017; Tempesta et al, 2015) that poor sleep quality increases the risk of developing physical and mental impairments. As the population ages, the need for caregivers will rise and addressing caregivers’ poor sleep quality may become a public health imperative, particularly as the physical and mental consequences of poor sleep quality in caregivers could also impact the care recipients they care for.…”
Section: Discussionmentioning
confidence: 81%
“…Research has found that caregivers have higher rates of depression and anxiety compared to non-caregivers (Haley et al, 2020; Pinquart & Sörensen, 2003), greater physical, psychological, and financial burdens, have less time for other family members, and may be less likely to participate in preventive health activities (Collins & Swartz, 2011). Caregiving has also been associated with poor sleep, which in turn can affect quality of life and health generally (Groeger et al, 2014; Mather et al, 2020; McCoy & Strecker, 2011; Narang et al, 2012; Petrov et al, 2018; Spira et al, 2010; Tapp et al, 2017; Tempesta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%